What Makes Online Synchronous Discussions Engaging?Results from a Case Study in Pre-service Teacher Education - Nicolaidou, Iolie; Nicolaou, Christiana T.; Constantinou, Constantinos P. (My University, 2006)
Over the last decade, there has been an increased use of computer mediated communication (CMC) within higher education. What type of instructor's role and what type of questions increase student participation and encourage responsiveness in synchronous online discussions? Is there a positive correlation between student participation in CMC and learning outcomes? This case study attempts to provide answers to these questions. Participants were 20 pre-service teachers who attended a blended e-learning science course. Content analysis (Cohen's kappa for interrater reliability=0.74) of transcripts from 9 synchronous discussions in WebCT revealed three important characteristics for learner-centered discussions: a structured approach of implementation, the instructor's role as the discussion facilitator and the use of questions that query understanding and encourage application, analysis and synthesis. Instructional strategies to improve online discussion implementation are also indicated.
Keywords: Learning Outcomes; Student Participation; Pre-Service Teacher Education